(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Fine art, like science, serves to know the world, life, nature, and the history of peoples. The emergence of fine art goes back to the time of the primitive community. At this time, people drew pictures of events, people and animals on stones, cut them and made sculptures of different shapes and contents. Since ancient times, people have believed that art, natural phenomena, and people’s interactions, activities, and behavior have a positive effect.